Dynamics of ventilatory pattern variability and Cardioventilatory Coupling during systemic inflammation in rats - Campanaro, Cara K.; Nethery, David E.; Guo, Fei; Kaffashi, Farhad; Loparo, Kenneth A.; Jacono, Frank J.; Dick, Thomas E.; Hsieh, Yee-Hsee (Frontiers in Network Physiology, 2023)
Biometrics of common physiologic signals can reflect health status. We have developed analytics to measure the predictability of ventilatory pattern variability (VPV, Non-Linear Complexity Index (NLCI) that quantifies the predictability of a continuous waveform associated with inhalation and exhalation) and the cardio-ventilatory coupling (CVC, the tendency of the last heartbeat in expiration to occur at preferred latency before the next inspiration). We hypothesized that measures of VPV and CVC are sensitive to the development of endotoxemia, which evoke neuroinflammation. To test this, we implanted Sprague Dawley male rats with BP transducers to monitor arterial blood pressure (BP). We recorded ventilatory waveforms and BP simultaneously using whole-body plethysmography in conjunction with BP transducer receivers. After baseline (BSLN) recordings, we injected lipopolysaccharide (LPS, n=8) or phosphate buffered saline (PBS, n=3) intraperitoneally on 3 consecutive days. We recorded for 4-6h after the injection, chose 3 epochs from each hour and analyzed VPV and CVC as well as heart rate variability (HRV). First, the responses to sepsis varied across rats, but within rats the repeated measures of NLCI, CVC, as well as respiratory frequency (fR), HR, BP and HRV had a low co-efficient of variation, (<0.2) at each time point. Second, HR, fR, and NLCI increased from BSLN on Days 1-3; whereas CVC decreased on Days 2 & 3. In contrast, changes in BP and the relative low-(LF) & high- frequency (HF) of HRV were not significant. The coefficient of variation decreased from BSLN to Day 3, except for CVC. Interestingly, NLCI increased before fR in LPS-treated rats. Finally, we histologically confirmed lung injury, systemic inflammation via ELISA and the presence of the proinflammatory cytokine, IL-1β, with immunohistochemistry in the ponto-medullary respiratory nuclei. Our findings support that NLCI reflects changes in the rat’s health induced by systemic injection of LPS and reflected in increases in HR and fR. CVC decreased over the course to the experiment. We conclude that NLCI shows a reliable increase in the predictability of the ventilatory waveform and (together with our previous work) may reflect action of inflammatory cytokine on the network generating respiration.